2018
DOI: 10.1089/scd.2017.0206
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Exposure to Simulated Hypergravity-Induced Changes in Proliferation, Morphology, and Gene Expression of Human Tendon Cells

Abstract: Gravity influences physical and biological processes, especially during development and homeostasis of several tissues in the human body. Studies under altered gravity have been receiving great attention toward a better understanding of microgravity-, hypogravity (<1 g)-, or hypergravity (>1 g)-induced alterations. In this work, the influence of simulated hypergravity over human tendon-derived cells (hTDCs) was studied at 5, 10, 15, and 20 g for 4 or 16 h, using a large diameter centrifuge. Main results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…In a similar study, an increase in actin fiber density, but not in number, was pointed even in low g forces [ 59 ]. The results of both studies are in accordance with even more recent research performed on human tendon cells, cultured in 15–20 g for 16 h [ 60 ].…”
Section: Effects Of Altered Gravity On Homo Sapiens and Other Vertebrate Speciessupporting
confidence: 91%
See 1 more Smart Citation
“…In a similar study, an increase in actin fiber density, but not in number, was pointed even in low g forces [ 59 ]. The results of both studies are in accordance with even more recent research performed on human tendon cells, cultured in 15–20 g for 16 h [ 60 ].…”
Section: Effects Of Altered Gravity On Homo Sapiens and Other Vertebrate Speciessupporting
confidence: 91%
“…In a similar study, an increase in actin fiber density, but not in number, was pointed even in low g forces [59]. The results of both studies are in accordance with even more recent research performed on human tendon cells, cultured in 15-20 g for 16 h [60]. Bradamante et al (2018) studied osteogenic stem cell differentiation in microgravity in order to discover how human bone marrow stem cells (hBMSCs) react to a two week exposure in ISS when treated with the osteo-inducer 1,25-dihydroxy vitamin D. Their results provide evidence of cell cycle arrest, although without any indications of adipogenesis, senescence and apoptosis.…”
Section: Gravity and The Musculoskeletal Systemsupporting
confidence: 90%
“…Until now, a number of studies were carried out under simulated conditions of unnatural gravity using ground-based facilities such as clinostats, random positioning machines, bioreactors, and parabolic flights for simulated microgravity (sµg) research [298][299][300], and well-designed centrifuges for hyper-gravity experiments [301,302]. Some real microgravity (µg) investigations were conducted in space on the International Space Station or onboard sounding rockets [303].…”
Section: Gravitational Forces Affecting Biomembranesmentioning
confidence: 99%
“…At the cellular level, it has been shown that microgravity alters the structure of cells, as well as their apoptotic and mitotic responses [6,7,8]. Hypergravity also has a relevant impact in cells behavior and gene expression [10,11,12,13]. However, specific modifications in gene expression, gene products, and related structural-functional phenotypic diversification due to sustained changes in gravity conditions remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%